Prevalence and economic importance of hydatidosis and fasciolosis in slaughtered cattle in Erzurum province of Turkey - Balkaya, Ibrahim; ŞImşek, Sami (Veteriner Fakultesi Dergisi, 2010)
The aim of this study was to detection of hydatidosis and fasciolosis prevalance in Erzurum province. For this aim this study was carried out 2088 cattle slaughtered in offical and a local slaughterhouses of Erzurum province between December 2008 and April 2009. Majority of examined cattle were female and local breed, the ages between 2-10 and almost all of feeding pasture. After the slaughter liver bile ducts were examined for Fasciola spp and mainly liver and lungs and also other inner organs for hydatid cysts. Out of 2088 cattle, 717 (34.3%) were found to be hydatic cyst positive. In these infected cattle, 520 (72.5%) were had hydatid cysts in their lungs and 83 (11.6%) were had cysts only in their livers, 109 (15.2%) were had both lungs and liver cysts, 4 (0.6%) were had spleen and only one (0.1%) was had heart cyst. Besides, 439 (21%) out of 2088 cattle were found as infected with Fasciola hepatica. If it is assumed that all livers infected with F. hepatica and hydatid cyst were completely disposed, totally 522 livers should be destroyed. The economic losses due to the fasciolosis was calculated as 17.560 Turkish Liras (TL) and this rate was 3.320 TL for hydatid cysts. Finally, total economic losses was estimated as 20.880 TL.
Erzurum'da kesilen sı?ırlarda hidatidosis ve fasciolosis'in yaygınlı?ı ve ekonomik önemi
Keywords: Cattle; Erzurum; Fasciola hepatica; Hydatid cyst; Prevalance